Effects of Mechanical Treatment on the Formation of Α-Al 2o3 From Gibbsite - Şakar Deliormanlı, Aylin; Çiftçioğlu, Muhsin; Polat, Hürriyet; Polat, Hürriyet; Çiftçioğlu, Muhsin; Şakar Deliormanlı, Aylin Müyesser (Trans Tech Publications, 2004)
In this study preparation of fine alpha alumina powders derived from Bayer gibbsite was studied. Preparation of the alumina powders was performed by decomposition of the gibbsite into transition alumina phase followed by controlled transformation to the alpha phase. Gibbsite was thermally treated at 350°C and 900°C to obtain a transition form of alumina. The purpose of the heat treatment at 350°C was to increase the surface area of the gibbsite particles and obtain a loosely packed structure that may reduce the size of the rather coarse precursor gibbsite during the grinding step. Mechanical treatment (by using ultrasonic forces and impact forces) was utilized to increase the transformation rate to the alpha alumina in the transition phase matrix and influence the nucleation and growth rate of the solid -solid phase transformation. These powders were calcined at 1100, 1200 and 1450°C for 1 to 8 hours. Results indicated that transformation to the alpha phase was accomplished in the powders preheated at 900°C, ultrasonically treated or ground, and then calcined at 1200°C for 2 to 8 hours or at 1450°C for 2 hours. Ultrasonic treatment accelerated the transformation rate to the alpha phase at 1100°C in 2 hours. Powders that were calcined at 1100 to 1200°C for 1 hour had a significant kappa content together with the alpha phase. Additionally the powder prepared without mechanical treatment and calcined at 1100°C was mainly in the kappa phase.
Proceedings of the 8th Conference and Exhibition of the European Ceramic Society; Istanbul; Turkey; 29 June 2003 through 3 July 2003
Keywords: α-Alumina; Gibbsite; Grinding; Phase transformation; Ultrasonic treatment; Aluminum compounds